FOOD WASTE ON ASSORTED STAKEHOLDERS TOWARDS A GREEN ECONOMY FOOD SECURITY - Maswadi, Maswadi; Kusrini, Novira; Aritonang, Marisi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Indonesia is the country with the second highest level of food waste in the world and the first in Southeast Asia. Therefore, Indonesia has the highest Global Hunger Index in Southeast Asia, second only to Timor Leste. This condition has continued to increase over the last twenty years compared to food loss. Therefore, Indonesia is increasingly vulnerable to food shortages. Food waste needs to be minimized to help meet future food needs. The aim of this research is to identify the factors that underlie consumer behavior in wasting food. Interviews were conducted with 273 respondents, especially in West Kalimantan, Indonesia.  The collected data was then analyzed using Structural Equation Modeling (SEM) through the AMOS 24 program. The findings in this research show that the five factors underlying consumer behavior, namely: food choices, shopping routines, food handling, waste prevention behavior, and recycling behavior have a negative effect. and significant to the amount of food waste. This means that, the better the food choices, shopping routines, food handling, waste prevention behavior, and recycling behavior, the smaller the amount of food waste produced. Other findings show that waste prevention behavior has the greatest influence on food waste. Efforts that consumers can make to reduce the amount of food waste at the household level are by increasing knowledge about good food choices, improving skills in processing and storing food, and committing to making a list of needs before shopping and complying with it.